49 The role and impact of a pharmacist in a multi-disciplinary a trial fibrillation clinic. (28th September 2016) - Morrissey, E; Pharithi, R; Collins, R; McManamly, C; Burke, C; Moore, D
Abstract : Introduction: Tallaght Hospital assesses and admits over 400 patients with a primary and 2, 100 patients with a secondary diagnosis of atrial fibrillation (AF) including almost 100 of our acute strokes. Almost all patients require primary and secondary prevention with anticoagulation. An interdisciplinary (Cardiology, Geriatric Medicine and Pharmacy) AF clinic was set up to ensure effective gold standard treatment of AF. Importance of pharmacy in multidisciplinary clinic was identified early for patients using direct oral anticoagulants (DOACs) and other cardiac drugs as medications for AF often have complex dosing schedules, many drug interactions and important counselling points which are most suitably managed by a pharmacist. The aim of this study was to look at the number of interventions made by the pharmacist on the dose or selection of anticoagulation treatment and the number of secondary interventions made. Methods: A treatment protocol was drafted and approved, highlighting the scope and framework for the pharmacist's involvement and their practising framework. A data collection form was designed based on guidance issued from the European Heart Rhythm Association (EHRA) and guidelines from European Society of Cardiology (ESC) for the Management of Atrial Fibrillation. Interventions were included if they were agreed and acted on by the cardiologist in the clinic. Data was analysed using Microsoft Excel. Results: To date 125 patient consultations were carried out by the pharmacist and the cardiologist. 15% of consultations by pharmacist resulted in a change of anticoagulation for the patient. These recommendations arose from issues such as changes in renal function, drug interactions and poor adherence. 50% of consultations by pharmacist resulted in secondary interventions Recommended. Conclusion: The high rate of interventions both on anticoagulation and rate control emphasises the importance of the AF clinic as a whole and the importance of pharmacist involvement. An audit on pharmacist interventions in this clinic will continue to strengthen the evidence for this role. References: Tallaght Hospital Medicines Guide 2016/17 p.541 Heidbuchel, et al . EHRA Practical Guide on the use of new oral anticoagulants in patients with non-valvular atrialfibrillation. Europace 2013;15 :625–51